Gabriel García Márquez new readings - McGuirk, Bernard; Cardwell, Richard Andrew (Cambridge Iberian and Latin American studies, 1987)
This volume of essays constitutes a critical reappraisal of a front-rank world author, Gabriel García Márquez, who was awarded the Nobel Prize for Literature in 1983. Apart from extending critical appreciation of his work to an English-reading public, its principal objective is to reflect the breadth and variety of critical approaches to literature applied to a single corpus of writing; here, the major novels (including Love in the Times of Cholera, 1986) and a selection of his short fiction are considered. The aim of this collection, given these dual objectives, is to extend knowledge of the work of García Márquez and introduce to both the general reader and to students of literature a plurality of current critical approaches to his rich variety of fictional techniques. The volume also includes a bibliography of criticism available in English and an English translation of the author's Stockholm Nobel acceptance address